1999
DOI: 10.1557/s1092578300003392
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ion Beam Etching of GaN

Abstract: We have investigated the use of focused ion beam (FIB) etching for the fabrication of GaN-based devices. Although work has shown that conventional reactive ion etching (RIE) is in most cases appropriate for the GaN device fabrication, the direct write facility of FIB etching -a well-established technique for optical mask repair and for IC failure analysis and repair -without the requirement for depositing an etch mask is invaluable. A gallium ion beam of about 20nm diameter was used to sputter GaN material. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…R a was found to be the most crucial factor in producing good surface quality of micrcomponents [14,15,16]. Researchers have found that the sidewall R a is estimated to be below 100 nm when sputtering GaN by using a lower beam current since a large beam diameter is produced when a high beam current is used [10,14]. Material removal rate, MRR in physical sputtering depends on parameters such as dwell time.…”
Section: Focused Ion Beam Systemmentioning
confidence: 99%
“…R a was found to be the most crucial factor in producing good surface quality of micrcomponents [14,15,16]. Researchers have found that the sidewall R a is estimated to be below 100 nm when sputtering GaN by using a lower beam current since a large beam diameter is produced when a high beam current is used [10,14]. Material removal rate, MRR in physical sputtering depends on parameters such as dwell time.…”
Section: Focused Ion Beam Systemmentioning
confidence: 99%
“…Reactive ion etching [3] and very recently wet etching techniques [4] have mostly been employed for the device fabrication; these, however, are not the preferred techniques for the nano-fabrication of ultra-small GaN-based devices. Focused ion beam (FIB) etching is one of the most promising techniques for the fine patterning of GaN, however, only basic etching parameters have been investigated so far [5,6]. In this paper, we report for the first time on the nano-fabrication of GaN into structures as small as 20 to 30 nm in diameter.…”
mentioning
confidence: 99%
“…The etch depth is proportional to the gallium ion beam dose, i.e. proportional to the gallium ion beam current per area times the etching time [5]. The pillar side walls are nearly vertical, the pillar tops are to some extent rounded.…”
mentioning
confidence: 99%
“…Gallium Nitride (GaN) is a widely applicable semiconductor material that has a high melting point and strong light sensitivity properties, which make it well suited for both high temperature devices and light detecting or emitting devices [29,30]. Unlike traditional methods of etching, the FIB does not need an etch mask for manipulation because of its local specificity and precision; this is a most valuable feature in semiconductor fabrication.…”
Section: Materials Characterization and Alterationmentioning
confidence: 99%
“…The edge sections were found to have a roughness below 0.1 μm, a quite favorable number. All in all, it was found that although slower than traditional methods, FIB etching on GaN proved to be more advantageous in its high quality production and versatility [30].…”
Section: Materials Characterization and Alterationmentioning
confidence: 99%